2021
DOI: 10.3389/fphy.2021.720533
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Characteristics of Coastal Wind Energy Resources in Zhejiang Province Based on ERA-Interim Data

Abstract: The reanalysis of sea surface wind speed is compared with the measured wind speed of five offshore wind towers in Zhejiang, China. The applicability of reanalysis data in the Zhejiang coastal sea surface and the climatic characteristics of sea surface wind power density is analyzed. Results show that the reanalysis of wind field data at the height of 10 m can well capture the wind field characteristics of the actual sea surface wind field. The sea surface wind power density effective hours increases from west … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…However, we include variables such as wind direction and surface roughness that allow enriching the potential of the data set for energy production analysis in future studies. Studies in which data sets similar to ours could contribute can be found in the area of economic analysis (see, e.g., [6][7][8][9][10]) or grid integration ( [11][12][13][14][15][16][17][18][19]) as well as in climate change analysis [20][21][22]. Among these papers, ref.…”
Section: Introductionmentioning
confidence: 91%
“…However, we include variables such as wind direction and surface roughness that allow enriching the potential of the data set for energy production analysis in future studies. Studies in which data sets similar to ours could contribute can be found in the area of economic analysis (see, e.g., [6][7][8][9][10]) or grid integration ( [11][12][13][14][15][16][17][18][19]) as well as in climate change analysis [20][21][22]. Among these papers, ref.…”
Section: Introductionmentioning
confidence: 91%
“…Global warming is one of the most challenging global issues [8][9][10]. However, because of the multiple scales of climate change effects, climates and natural systems at different spatiotemporal scales show different change characteristics [11][12][13]. A key scientific issue in ecometeorological research is how to objectively evaluate the suitability of summer climate as a basis for recommending suitable summer tourism city and scenic spot destinations [14,15].…”
Section: Introductionmentioning
confidence: 99%